"Produção otimizada de ácido penicílico pelo fungo endofítico Penicillium rolfsii com aplicação em fitopatógenos causadores de doenças em Phaseolus vulgaris L. " - LAÍS ROCHA DE SÁ (2024)
With the increasing demand for food, it is necessary to optimize food production without expanding planting areas. One way to achieve this goal is to reduce production losses caused by phytopathogens in legumes, which are one of the main sources of carbohydrates, fiber, proteins, and minerals for Brazilians. Among the most consumed species is Phaseolus vulgaris L. (common bean), whose production is affected by the fungi Macrophomina phaseolina, Rhizoctonia solani, Fusarium sp., and Colletotrichum lindemuthianum and by the bacterium Xanthomonas phaseoli pv. phaseoli. The chemical pesticides used to control infections caused by these organisms are classified as harmful to the environment, and resistant strains to these compounds already exist. Therefore, it is urgent to seek new compounds that do not harm the environment and can inhibit the action of phytopathogens. One alternative is the antimicrobial compounds produced by endophytic fungi, such as penicillic acid. In this context, the aim of this work was to produce an extract containing penicillic acid by the endophytic fungus Penicillium rolfsii 1IP2F2 and to evaluate its ability to inhibit the growth of the phytopathogens M. phaseolina, R. solani, Fusarium sp., C. lindemuthianum, and X. phaseoli pv. phaseoli in in vitro and in vivo assays on bean seeds. This endophytic fungus was isolated from Bromelia balansae Mez. (Bromeliaceae), and in direct antagonism confrontation tests against the phytopathogens M. phaseolina, R. solani, and Fusarium sp., the fungus P. rolfsii was ineffective. However, its crude extract from the culture medium (Eb-Pen) containing 270.4 µg/mL of penicillic acid was active in inhibiting the growth of the bacterium X. phaseoli pv. phaseoli, and the ethyl acetate extract (Eb-Pen-Ac) with 142 µg/mL of penicillic acid inhibited the fungi C. lindemuthianum, Fusarium sp., and R. solani, and inhibited M. phaseolina at 284 µg/mL in microculture tests. No inhibition of bean germination was observed when treated with 142 to 497 µg/mL of the acid. In the bean seed tests treated with Eb-Pen-Ac and contaminated with the phytopathogenic fungi, it was observed that treated seeds showed no symptoms of infection by R. solani, even when contaminated. From the results obtained, it is possible to suggest the use of penicillic acid in the control of diseases caused by bacteria and fungi through seed treatment, as long as it is in low concentrations.